La pleine conscience comme premier temps thérapeutique des troubles anxieux chez l’enfant - de Becker, Emmanuel (Annales médico psychologiques, 2020)
L’angoisse excessive ou pathologique de l’enfant représente un objet courant de consultation pédopsychiatrique, qu’il soit initié par les membres de l’entourage familial ou par les professionnels de l’enfance. Il n’est guère toujours aisé de distinguer l’angoisse existentielle que tout enfant appréhende au cours de son développement de celle qui prend un accent délétère, dommageable à son épanouissement. L’article propose de se pencher sur les troubles anxieux chez l’enfant en rappelant quelques définitions et manifestations cliniques avant d’ouvrir la question de la place de la pleine conscience dans l’abord thérapeutique. La pleine conscience en tant qu’approche non invasive nous apparaît intéressante dans les troubles anxieux chez l’enfant et ce dans une triple finalité. Elle permet d’abord de mettre le jeune patient en confiance dans la perspective de l’établissement d’un lien transférentiel. Par ailleurs, cette technique contient en soi un effet anxiolytique non négligeable dont les répercussions positives dépassent la seule personne de l’enfant concerné. Enfin, comme cette première approche thérapeutique s’avère à la fois surprenante, attrayante, engageante, l’enfant accepte plus volontiers de poursuivre la démarche de traitement. Requests for advice, advice and treatment in child-child psychiatry are experiencing an exponential explosion, as seen by clinicians and those involved in childhood; it is also relayed to the competent health authorities. The child's excessive or pathological anguish is a common subject of child psychiatric consultation, whether initiated by members of the family or by child care professionals. Symptomatology is varied, multi-faceted and comorbidity frequent. However, it is not always easy to distinguish the existential anguish that every child apprehends during his development from that which takes on a deleterious accent, harmful to his development. The article proposes to address anxiety disorders in children by recalling some clinical definitions and manifestations before opening the question of the place of mindfulness in the therapeutic axe. We propose to repeat the main elements of several concepts such as anxiety, anxiety and stress. In general, anxiety can be understood as a painful sensation of deep discomfort, determined by the diffuse impression of a relatively vague but imminent danger, before which one remains unarmed and powerless. It is usually accompanied by neuro-vegetative changes. Anxiety will be understood differently depending on the theoretical reference. Anxiety is manifested by distress, a sense of threat or fear. It also corresponds to an emotional state characterized by a feeling of worry, insecurity, marked by the apprehension of an indeterminate danger before which one feels powerless. Thought holds a prominent place. There is also the notion of stress which reflects all the responses to pressures and constraints arising from the environment. The body mobilizes psychophysiologically to escape danger. The anxiety disorder manifests itself in very different ways depending on the children, their age, their personality and the type of disturbance. Let us emphasize at the outset how anxiety is potentially masked by hyperactivity, agitation or other behavioural disorders. Anxiety disorders are often associated with learning difficulties. The recommended management of anxiety disorders in the first instance is psychotherapy. It may even constitute the only treatment or be associated for example with the psychopharmacological approach, depending on the severity of the disorder, this without neglecting probable interventions in the contextual reality of the child concerned. In fact, let us recall how much the young subject is dependent on his environment and how much interference with it can seriously affect his psychic state. If the symptoms are intense, disabling and/or psychotherapy is not sufficient to contain them, a psychopharmacological treatment may be considered, combined with other therapeutic axes. The axis of the medication should also be used in the presence of a harmful comorbidity. Given the neuro-vegetative effects of anxiety disorders, before resorting to psychopharmacological treatment, we recommend that we favour the relaxation techniques often appreciated by the child. Let's continue thinking about treatments by focusing on a specific approach. The intervention programs using so-called mindfulness meditation aim to encourage the individual to welcome his thoughts, emotions and sensations. In a general way, mindfulness allows us to devote all of our attention to the present moment without passing judgment in order to be in the most contact with our lived experiences. Beyond a fashion effect, mindfulness provides a promising perspective for acting on the signs of anxiety, stress in children and adults, regardless of the presence of mental health disruption in the subject. This being the case, the effectiveness of this practice in anxiety disorders by improving the symptoms of the child is now recognized. This technique has a positive influence on several other variables such as creativity, cognitive flexibility, concentration in learning. On the other hand, mindfulness visibly increases social abilities. There is a correlation between regular participation in meditation exercises and improvement of the child's well-being and a decrease in anxiety symptoms.